2004
DOI: 10.1111/j.1365-2141.2004.04864.x
|View full text |Cite
|
Sign up to set email alerts
|

Ability of myeloma cells to secrete macrophage inflammatory protein (MIP)‐1α and MIP‐1β correlates with lytic bone lesions in patients with multiple myeloma

Abstract: These results provide further evidence for a causal role of MIP-1a and MIP1b in the development of lytic bone lesions, and suggest that MM cells suppress osteoblastic bone formation to cause an imbalance of bone turnover and development of destructive bone lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
3
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 18 publications
2
44
3
1
Order By: Relevance
“…CCL3 and CCL4 RNA expression in MM cell lines were analysed with RT-PCR and the secretion to the cell culture supernatant by MM cell lines and magnetic bead separated MM PCs from myeloma patients, by ELISA technique (Abe et al, 2002;Hashimoto et al, 2004). The differences in techniques, and especially, in analysed material (cell lines vs. MM patient PCs) may explain the discrepancy between literature data and ours.…”
Section: Ccl3 and Ccl4contrasting
confidence: 44%
See 2 more Smart Citations
“…CCL3 and CCL4 RNA expression in MM cell lines were analysed with RT-PCR and the secretion to the cell culture supernatant by MM cell lines and magnetic bead separated MM PCs from myeloma patients, by ELISA technique (Abe et al, 2002;Hashimoto et al, 2004). The differences in techniques, and especially, in analysed material (cell lines vs. MM patient PCs) may explain the discrepancy between literature data and ours.…”
Section: Ccl3 and Ccl4contrasting
confidence: 44%
“…In a semi-quantitative manner with RT-PCR and agarose gel electrophoresis it has been found that CCL3 and CCL4 were produced and secreted by a majority of MM cell lines, and is secreted to the culture supernatants by magnetic bead-separated MM PCs from MM patients (Abe et al, 2002). A correlation between MIP-1a and -b secretion in supernatants of cultured MM cells and the severity of OBD was demonstrated with enzyme-linked immunosorbent assay (ELISA) (Abe et al, 2002;Hashimoto et al, 2004).…”
Section: Ccl3 and Ccl4mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, increasing b leads to more bone destruction, higher tumour burden and faster tumour progression. This behaviour is observed clinically, patients with higher MIP-1a levels (increasing b) tend to have more bone resorption and lytic bone lesions (Terpos et al, 2003;Hashimoto et al, 2004) and shorter survival due to a higher tumour burden (Terpos et al, 2003). Consequently, therapies which suppress or reduce b (inhibiting, e.g., MIP-1a secretion or IL-1b (Lust et al, 2009;Dinarello, 2009b)) should decrease the number of lytic lesions and the speed of disease progression, prolonging survival (Choi et al, 2001).…”
Section: Resultsmentioning
confidence: 73%
“…Levels of MIP-1a in marrow of patients with myeloma range between 100 and 2000 pg/ml. 27 Similarly, Hashimoto and co-workers 29 have shown that elevated levels of MIP-1a and MIP-1b are both detectable in patients with myeloma, and that high levels of MIP-1a are associated with an extremely poor prognosis. Most recently, Magrangeas and co-workers 30 have shown by gene-expression profiling that MIP-1a expression is the gene most highly correlated with bone destruction in myeloma patients.…”
Section: Macrophage Inflammatory Protein-1amentioning
confidence: 99%